Communication and awareness on a new vaccine: a cross-sectional study in a tertiary care hospital of West Bengal - Chakraborty, Arup; Datta, Mousumi; Guchhait, Debjani; Gupta, Shibaji (International Journal Of Community Medicine And Public Health, 2019)
Background: Japanese encephalitis (JE) vaccination in India started in 2006 with SA-14-14-2 live attenuated JE vaccine (JEV) following large outbreaks of JE in some districts of Eastern Uttar Pradesh and Bihar in 2005. Age groups 1-15 yrs are first vaccinated with a single dose of JEV in a campaign mode followed by integration of this vaccine in routine immunization. It is beyond doubt that added to vaccination campaigns, proper awareness on JE can play significant role in controlling the disease. Methods: An observational study with cross sectional design was conducted in Kolkata Medical College and Hospital, Kolkata during JE Vaccination campaign during January, 2018 among 85 respondents, to assess the awareness on JE, among care-givers who brought their children for vaccination at the immunization clinic. Results: It was found that only 37.6% the respondents attending the campaign knew the name of the disease; 17.6% respondents were aware about disease transmission, and 5.9% could state two or more clinical features that might be associated with Japanese Encephalitis. 69.4% had no knowledge of up to what age JE vaccines can be administered; 23.5% said it can be administered till the beneficiaries attain fifteen years of age. Conclusions: IEC activities during JE vaccination campaign was not able raise awareness on JE to the desired level. However beneficiaries were informed about service availability and could be mobilised to come for vaccination.